Diseño de una granja agroturística en la unidad educativa Eloy Alfaro de Huigra, cantón Alausí - Núñez Cuenca, Hernán Mauricio (2025)
The research arises from the need to diversify the economic activity of Huigra and expand its tourism offerings by leveraging the available resources and areas. An important space belonging to Eloy Alfaro High School has been identified as having favorable soil for agricultural production. This proposal suggests the possibility of utilizing this area. The objective is to design an agrotourism farm to benefit the institution's educational community, going beyond merely providing a recreational space. It also aims to contribute to the dynamism of tourism activity. To achieve this goal, theoretical research was conducted on topics related to the implementation of agrotourism farms, as well as field research through observation, followed by interviews and surveys with local residents. This process revealed the importance of agricultural activity in the area and the local perception of tourism as an opportunity for economic development. As a result, this proposal outlines the elements necessary for designing an agrotourism farm for the Institution. Consequently, it is concluded that the development of such projects not only benefits the educational community but also provides a formative meeting space, useful for training and supporting local entrepreneurship, while raising awareness of the importance of sustainable tourism in the region.